Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,434 questions

17,804 answers

1,438 comments

48,081 users

Differentiation help please?

0 votes
1. Given that xy = 8100, find the value of dy/dx when y = 180.
2. The gradient of the curve y = px + q/x^2 at the point (1,9) is 3. Calculate the values of p and q.
3. Differentiate (3t^2 - 4t)(t + 1)/2(square root t) with respect to t.
asked Feb 18, 2013 in CALCULUS by homeworkhelp Mentor

4 Answers

+1 vote

xy = 8100

Substitute y = 180 in the equation.

x(180) = 8100.

Divide each side by 180.

x = 8100/180 = 45.

Take xy = 8100.

Apply 'derivative with respect to x' each side.

(d/dx)(xy) = (d/dx)(8100)

The Product Rule (UV)' = U'V + UV' and derivative of constant is 0.

x'y + xy' = 0

(1)y + xy' = 0

Substitute x = 45 and y = 180 in the equation.

180 + 45(y') = 0

Subtract 180 from each side.

45(y') = -180

y' = -4

Therefore the value of (dy/dx) = -4.

answered Feb 18, 2013 by britally Apprentice
+1 vote

3). (3t2 - 4t)(t + 1)/2

FOIL method: the product of two binomials is the sum of the products of the First terms, the Outer terms, the Inner terms and the Last terms.

[(3t2)t + (3t2)1 - (4t)t - (4t)1]/2.

[3t3 + 3t2 - 4t2 - 4t]/2

[3t3 - t2 - 4t]/2

Apply 'derivative with respect to t' each side.

[(d/dt)3t3 - (d/dt)t2 - (d/dt)4t]/2

Power Rule of Derivative (d/dx)(xn) = nxn-1

[3(3t2) - (2t) - 4]/2

[9t2 - 2t - 4]/2

9t2/2 - 2t/2 - 4/2

(9/2)t2 - t - 2.

answered Feb 18, 2013 by britally Apprentice
+1 vote

2). The gradient of the curve y = px + q/x2 at the point (1,9) is 3

i.e. y' = 3 at (1, 9)

9 = p(1) + q/(1)2

9 = p + q -----------------> (1)

Take y = px + q/x2

Mathematical rule: 1/a = a-1

y = px + qx-2

Apply derivative each side.

dy/dx = (d/dx)(px + qx-2)

y' = (d/dx)(px) + (d/dx)(qx-2)

Power Rule of Derivative (d/dx)(xn) = nxn-1

y' = p(1) + q(-2x-3)

y' = p - 2q/x3

Substitute x = 1 and y' = 3 in the equation.

3 = p - 2q/13

3 = p - 2q------------>(2)

Subtract equation (1) and equation (2).

p + q = 9

p - 2q = 3

--------------------

3q = 6

Divide each side by 3.

q = 6/3 = 2

Substitute q = 2 in the equation (1)

p + 2 = 9

Subtract 2 from each side.

p = 9 - 2 = 7

Therefore p = 7 and q = 2.

answered Feb 18, 2013 by britally Apprentice
0 votes

image = image

Use product rule : .

image

image

Use power rule : .

image

image

image

image

image

image

image.

Therefore, image image.

answered Jul 15, 2014 by lilly Expert

Related questions

asked Nov 5, 2014 in CALCULUS by anonymous
asked Jul 23, 2014 in CALCULUS by anonymous
asked Oct 4, 2014 in PRECALCULUS by anonymous
asked Nov 5, 2014 in CALCULUS by anonymous
...